Das hydrologisch-geomorphologische Versuchsgebiet Hollmuth des Geographischen Instituts der Universität Heidelberg - Barsch, Dietrich; Flügel, Wolfgang-Albert (ERDKUNDE, 1978)
In the first phase of our “Interflow”, research project (begun in February 1976) a hydrological test field was prepared in which we installed different instruments to measure the important components of water supply. To overcome the difficulty of measuring interflow directly under field conditions we constructed and installed special measurement equipment which continued to work satisfactorily. To determine by indirect method the movement of soil water in the slope during times of low water content 40 tensiometers were installed. These measure the hydraulic gradient in the soil as the sum of the moisture potential if and the vertical gradient z. In addition to these field measurments the hydraulic conductivity of the soil is determined for different moisture contents G and depths of the soil monoliths in our laboratory. The results of the measurments in the field and the laboratory were computed by EDV. Special computer programs were written by us to combine all the important hydrological and climatological parameters and to compute the quantity of the interflow as well as the total water balance of this small system. This phase will be finished in July 1977. In the second phase we will enlarge our project to include the whole system of the Elsenz river. In this phase it is planned to work particularly on problem of the importance of soil moisture physics, soil moisture chemistry, the chemistry of groundwater and run-off and their relations to the water supply of this system.